PENATALAKSANAAN TEKNIK PEMERIKSAAN BNO IVP PADA KASUS URETEROLITHIASIS DI INSTALASI RADIOLOGI RUMAH SAKIT PEKANBARU MEDICAL CENTER - Fariuzi (Medical Imaging and Radiation Protection Research Journal, 2023)
BNO IVP radiographic examination is an examination conducted to see the anatomy and function of the urinary tract by injecting a contrast agent into the body through the veins. In the BNO IVP examination, several photos are taken at different minutes. Plain abdominal radiographs are performed with AP projection, 5-minute photos with AP projection, 15-minute photos with oblique projection, 45-minute photos with AP projection, and post-mixi photos with AP erect projection. While the BNO IVP examination at Pekanbaru Medical Center Hospital uses 1 routine projection, namely AP projection on plain abdominal radiographs, 5-minute photos, 15-minute photos, 30-minute photos, 45-minute photos and post-mixi photos so that there is a difference between theory and the field. The purpose of this study was to determine the management of BNO IVP examination techniques with clinical Ureterolithiasis in the Radiology Installation of Pekanbaru Medical Center Hospital using AP projections (plain abdominal radiographs, 5 minutes, 15 minutes, 45 minutes and post-mixi photos). In this study, descriptive qualitative research was used by describing the research results in narrative form. The research results were obtained through several stages, namely observation, interviews, and documentation. The study was conducted at Pekanbaru Medical Center Hospital in November-December 2022. The management of the BNO IVP examination technique for clinical ureterolithiasis at Pekanbaru Medical Center Hospital used AP projection. AP projection was used in each phase of the image (plain abdominal radiograph, 5-minute, 15-minute, 30-minute, 45-minute, and post-mixi photo) to confirm the diagnosis.